Social media wise education: Improving the digital literacy of vocational school students through Instagram - Ulfa, Marissa; Lubis, Metha (Penamas: Journal of Community Service, 2025)
The COVID-19 pandemic has led to significant changes in the education system, including in Indonesia, with the implementation of online learning. This condition has encouraged an increase in internet and social media use among teenagers. Student activities on social media, especially Instagram, have increased significantly, but have not been balanced with adequate digital literacy skills. This Community Service activity aims to provide education to students of SMK Islamiyah Serua Ciputat about the wise and responsible use of social media, as well as encourage the involvement of teachers and parents in the online mentoring process. The implementation method includes initial observation, interactive counselling, positive Instagram content visualisation training, and practical assistance involving lecturers, teachers, and students. The results of the activity showed that students experienced an increase in understanding related to social media ethics, skills in creating positive content, and awareness of the importance of critical thinking before sharing information on social media. Additionally, teachers and school staff play an active role in supervising student activities both during and after the event. This program is expected to be the first step in forming a smart, critical, and responsible digital generation on social media.